Penggunaan Microsoft Excel Guna Peningkatan Efektivitas dan Efisiensi Perhitungan Realisasi Pengiriman Produk di Perusahaan AMDK - Jaryanto Jaryanto; Mufti Zahroh Latifah Auladana; Ika Putri Nur Rahmawati; Rizki Abdul Bahri (Jurnal Pelayanan dan Pengabdian Masyarakat Indonesia, 2023)
This study aims to develop the use of Microsoft Excel for calculating the realization of product delivery at Bottled Water Companies. The research method that the author uses is descriptive qualitative. The results of this study indicate that using Microsoft Excel to calculate product delivery realization will be more effective and efficient than doing it manually. Based on several stages of data collection, Microsoft Excel is considered to be able to facilitate work related to numbers in bottled water companies.